Interdigit force coordination in visually guided pinch: studies of dynamic isometric pinch control in adults, typically developing children, and adolescents with Down syndrome. - Moerchen VA (Interdigit Force Coordination in Visually Guided Pinch: Studies of Dynamic Isometric Pinch Control in Adults, Typically Developing Children & Adolescents With Down Syndrome, 2002)
Coordination of submaximal isometric thumb (F[subscript]t) and index finger (F[subscript]i) forces in adults, children, and adolescents with Down syndrome was examined in a visually guided pinch force task. The digit forces were measured using a pinch apparatus that had two conditions: (1) The pivot condition wherein the relationship of digit forces was mechanically constrained, and (2) the fixed condition wherein the organization of digit forces was not constrained, theoretically allowing the neuromotor system to select a preferred pattern of interdigit coordination. The target was present throughout the trial to reduce the cognitive demands of the task, with a target force level that varied between 15-35% of each participant's maximal voluntary pinch force. The target consisted of a single-cycle sine wave, presented with positive or negative target sense so as to vary the order of higher versus lower force magnitude components of the sine wave. The effects of force magnitude and direction of force change on measures of visuomotor force accuracy and interdigit force coordination were also examined. Three studies were reported. Study 1 described a preferred pattern of interdigit coordination of F[subscript] t = F[subscript]i among adults, where this coordination appeared to be destabilized by lower force magnitudes combined with decreasing force. Anesthetization trials provided support for refinement of interdigit force coordination by rapidly adapting afferents within the digit tips. Study 2 described age-related trends in interdigit coordination where F[subscript]t = F[subscript]i emerged at younger ages when constrained, with a trend for this to become the preferred pattern of coordination with age. Additionally, parallel feedforward processing of interdigit coordination and pattern accuracy was proposed to account for an increased ability with age to vary digit forces without destabilizing pattern accuracy of the digit forces relative to the target. Study 3 provided preliminary data on two individuals with Down syndrome, supporting an ability to perform the task, and an ability to respond to mechanical constraints to produce the F[subscript]t = F[subscript]i pattern of coordination. A conceptual model for visually guided pinch force coordination was proposed.